HUMANISME TEOSENTRIS DALAM IDEOLOGI PENDIDIKAN ISLAM - Kurnialoh, Nasri (LPPM STAI Haji Agus Salim, 2024)
Abstract Some Islamic educational institutions only focus on philosophical perspectives without placing sufficient emphasis on human qualities. This can cause a gap between in-depth and material perspectives in schools. This type of written research, with documentation and scientific techniques limited to books, but also other supporting references. The research results obtained are that there is theocentric humanism as a paradigmatic reasoning choice in the contemporary school philosophy battle, by introducing the idea of ??theocentrism (tawhidi) as a guideline, as well as ghayatul hayat (all the goals of life). As well as Islamic Humanism which relies on human instincts as expressed in the Koran. This is not quite the same as other common Humanism has taken human ethics entirely from religion by discrediting God, as expressed in deep training in His proportions with moral simplicity can be achieved without belief in God. Therefore, it is very important to utilize theocentric humanism as an idea for the philosophical worldview of Islamic education. Keywords: Humanism, Theocentrism, Islamic Education Abstrak Beberapa lembaga pendidikan Islam hanya fokus pada perspektif filosofis tanpa memberikan penekanan yang cukup pada kualitas manusia. Hal ini dapat menyebabkan ketimpangan antara perspektif mendalam dan material di sekolah. Jenis penelitian tertulis, dengan teknik dokumentasi dan ilmiah terbatas pada buku, namun juga referensi lain mendukung. Hasil penelitian yang diperoleh adalah terdapat humanisme teosentris sebagai pilihan penalaran paradigmatik dalam pertarungan filsafat sekolah kontemporer, dengan memperkenalkan gagasan teosentrisme (tauhidi) sebagai pedoman, serta ghayatul hayat (segala tujuan hidup). Serta dengan Humanisme Islam yang bergantung pada naluri manusia seperti yang diungkapkan dalam Alquran. Hal ini tidak persis sama dengan Humanisme umum lainnya telah mengambil etika manusia sepenuhnya dari agama dengan mendiskreditkannya Tuhan, sebagaimana diungkapkan dalam pelatihan mendalam sesuai proporsi-Nya dengan kesederhanaan moral dapat dicapai tanpa keyakinan kepada Tuhan. Oleh karena itu, sangat penting untuk memanfaatkan humanisme teosentris menjadi ide pandangan dunia filosofis pendidikan Islam. Kata Kunci: Humanisme, Teosentris, Pendidikan Islam